Service Learning in Public Health: Exploring the Benefit to Host Agencies in CDC's Public Health Associate Program. Issue 5 (September 2017) - Wigington, Corinne J.; Sobelson, Robyn K.; Duncan, Heather L.; Young, Andrea C.
Abstract : The "learn by doing" approach to training is common in the public health field and is a core component of service-learning programs. Trainee satisfaction, learning, and application of learning have been studied. What is less understood is the perspective of the agencies that host trainees. This study aimed to identify whether and how the Centers for Disease Control and Prevention's Public Health Associate Program (PHAP) adds value to the agencies that host trainees during 2-year field assignments. An exploratory, qualitative study design consisting of 9 semistructured telephone interviews with PHAP host agency supervisors was used. Results suggested that PHAP increased host agencies' capacity by assigning capable trainees to host agencies. Trainees made quality contributions that led to agency- and/or community-wide improvements and positively affected the agencies' culture. Further evaluation of the host perspective is necessary; as coupled with the trainee's perspective, it will provide a more holistic understanding of program value.